OP0020 Tumour necrosis factor alpha acts directly on osteoclast formation by synovial mcrophages and monocytes in rheumatoid arthritis. (1st June 2001) - Fujikawa, Y; Kudo, O; Taira, H; Itonaga, I; Torisu, T
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease of unknown aetiology that results in progressive destruction of bone and cartilage in affected joints. It has been reported that in mouse bone marrow cell cultures TNF-alpha directly induces osteoclast formation and IL-1alpha stimulates osteoclast activation, and that this osteoclast formation and activation is independent of osteoprotegerin ligand (OPGL) signalling system. 1, 2 Objectives: TNF-alpha and IL-1alpha considered master cytokines in the process of RA but little is known about the direct effects of these cytokines on development of human osteoclasts. This study aims to determine the role of TNF-alpha and IL-1alpha, on synovial macrophage- and monocyte-osteoclast differentiation in RA. Methods: Macrophages and monocytes isolated from RA patients were cultured with TNF-alpha and/or IL-1alpha on glass coverslips and dentine slices in the presence of M-CSF. Anti-TNFalpha, anti-IL-1alpha and osteoprotegerin (OPG) was added to this cultures. Cultures were assessed for cytochemical and functional evidence of osteoclast differentiation. Results: The addition of TNF-alpha and M-CSF was sufficient to induce RA synovial macrophage- and monocyte-osteoclast differentiation in the absence of OPGL. This was evidenced by the formation of tartrate-resistant acid phosphatase (TRAP), vitronectin receptor, cathepsin K-positive multinucleated cells on glass coverslips and lacunar resorption pits on dentine slices. When IL-1alpha was added to this cultures together with TNF-alpha, the number of lacunar resorption pits were increased. It was found that anti-TNF-alpha inhibited osteoclast formation by RA synovial macrophages and monocytes and that although the number of TRAP-positive multinucleated cells was not changed, inhibition of pit formation was seen when anti-IL-1alpha was added to RA macrophage and monocyte cultures. OPG, however, showed no effect on osteoclast formation and activation induced by TNF-alpha and IL-1alpha. Conclusion: This study has shown that TNF-alpha induces RA synovial macrophage- and monocyte-osteoclast differentiation and that IL-1alpha activates osteoclasts to resorb bone. This osteoclast formation and activation is independent of OPGL signalling system. The new mechanism, inflammatory bone resorption, may represent an important role in the RA joint destruction and osteoporosis. References: Kobayashi K, Takahashi N, Jimi E, et al . Tumor necrosis factor alpha stimulates osteoclast differentiation by a mechanism independent of the ODF/RANKL-RANK interaction. J Exp Med. 2000;191: 275–86 Azuma Y, Kaji K, Katogi R, Takeshita S, Kudo A. Tumor necrosis factor-alpha induces differentiation of and bone resorption by osteoclasts. J Biol Chem. 2000;275:4858–64